Fatigue properties of low carbon steel strengthened by static or dynamic work hardening - Michel, Ján (Kovine zlitine tehnologije, 1998)
The influence of strain rate on mechanical properties and fatigue resistance of low carbon steel (C content 0.04%) is shown. Experimental results are analysed and relations derived describing the dependence of yield strength and ultimate tensile strength on prior strain rate in the range from ?$10^{-3}$? to ?$10^{-3}s^{-1}$?. The effect onfatigue resistanc was analysed, too. The impact hardened steel showed higher fatigue properties. Explanations are sought analyzing differences in microstructure and substructure of steel work hardened by static or impact strain.
Keywords: jeklo; mehanske lastnosti; trdnost; mikrostruktura